2012
DOI: 10.1142/s0219024912500161
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Bias Simulation Scheme for the Sabr Stochastic Volatility Model

Abstract: The Stochastic Alpha Beta Rho Stochastic Volatility (SABR-SV) model is widely used in the financial industry for the pricing of fixed income instruments. In this paper we develop a low-bias simulation scheme for the SABR-SV model, which deals efficiently with (undesired) possible negative values in the asset price process, the martingale property of the discrete scheme and the discretization bias of commonly used Euler discretization schemes. The proposed algorithm is based the analytic properties of the gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 25 publications
0
56
0
Order By: Relevance
“…Milstein-based Monte Carlo simulation is employed here as a reference for our one time-step simulation. In [24] , the authors have shown that the Milstein scheme is relatively stable when applied for the SABR model compared to the Euler or log-Euler schemes. In Fig.…”
Section: Pricing European Options By the One-step Sabr Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Milstein-based Monte Carlo simulation is employed here as a reference for our one time-step simulation. In [24] , the authors have shown that the Milstein scheme is relatively stable when applied for the SABR model compared to the Euler or log-Euler schemes. In Fig.…”
Section: Pricing European Options By the One-step Sabr Methodsmentioning
confidence: 99%
“…However some recent developments make this computation affordable. In [24] , Chen et al proposed a forward asset simulation based on a combination of moment-matching (Quadratic Gaussian) and enhanced direct inversion procedures. We employ this technique also here.…”
Section: Simulation Of S ( T ) Given S (0) σ ( T ) and T 0 σ 2 (S )D Smentioning
confidence: 99%
See 3 more Smart Citations